On the neural implementation of the speed-accuracy trade-off - Standage, Dominic; Blohm, Gunnar; Dorris, Michael C. (Frontiers in Neuroscience, 2014)
Decisions are faster and less accurate when conditions favour speed, and are slower and more accurate when they favour accuracy. This phenomenon is referred to as the speed-accuracy trade-off (SAT). Behavioural studies of the SAT have a long history, and the data from these studies are well characterized within the framework of bounded integration. According to this framework, decision makers accumulate noisy evidence until the running total for one of the alternatives reaches a bound. Lower and higher bounds favour speed and accuracy respectively, each at the expense of the other. Studies addressing the neural implementation of these computations are a recent development in neuroscience. In this review, we describe the experimental and theoretical evidence provided by these studies. We structure the review according to the framework of bounded integration, describing evidence for (1) the modulation of the encoding of evidence under conditions favouring speed or accuracy, (2) the modulation of the integration of encoded evidence, and (3) the modulation of the amount of integrated evidence sufficient to make a choice. We discuss commonalities and differences between the proposed neural mechanisms, some of their assumptions and simplifications, and open questions for future work. We close by offering a unifying hypothesis on the present state of play of this nascent research field.